Impacts of tourism and fire on ground-dwelling insect diversity in tropical pine forests of South Sulawesi, Indonesia - ANDI SADAPOTTO; SANDRA ANGELICA PUTRI CHRISTINE; ANDI PRASTIYO (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Sadapotto A, Christine SAP, Prastiyo A. 2025. Impacts of tourism and fire on ground-dwelling insect diversity in tropical pine forests of South Sulawesi, Indonesia. Biodiversitas 26: 5109-5117. Ground-dwelling insects serve as sensitive bioindicators of environmental change in tropical pine forests. This study aimed to compare the structure of ground-dwelling insect communities across three management areas of the Tala-Tala pine forest, South Sulawesi, Indonesia, namely the tourism area, non-tourism area, and post-fire area. This is the first study of ground-dwelling insect communities in Sulawesi's tropical pine forests. Sampling was conducted using multiple insect collection techniques, and ecological indices were applied to evaluate diversity, richness, evenness, and dominance. Statistical analyses were employed to compare land-use types and to assess their relationships with environmental factors. Diversity and evenness were lower in protected areas, whereas the tourism zone exhibited higher richness and dominance. Statistical analysis indicated significant (p<0.05) differences among land-use types in Shannon diversity, species richness, evenness, and dominance indices. Person correlation analysis showed a very strong negative correlation between diversity and dominance (r: -0.99), and a strong positive correlation between richness and soil pH (r: 0.99). Cluster analysis grouped the post-fire and tourism habitats, indicating similar disturbance levels, while PCA revealed that distinct environmental variables and ecological indices influenced each land-use type. The findings suggested that integrating biodiversity-friendly tourism practices with targeted post-fire habitat restoration supported insect diversity. These approaches also sustained the ecological and recreational value of tropical pine forests.